Properties of Poly-γ-Glutamic Acid Producing-Bacillus Species Isolated From Ogi Liquor and Lemon-Ogi Liquor - Ajayeoba, Titilayo A.; Dula, Stanley; Ijabadeniyi, Oluwatosin A. (Frontiers in Microbiology, 2019)
Poly-γ-glutamic acid (γPGA) is a natural and promising biopolymer synthesized by Bacillus spp. during fermentation. This study isolated Bacillus spp. from ogi steep liquor (OSL) and lemon-ogi steep liquor (LOSL) using standard methods and determined the γPGA-producing ability. The antimicrobial and angiotensin-converting enzyme (ACE) inhibitory activities of γPGA polymer were evaluated and isolates were sequenced. Four isolates (TA004, TA006, TA011, TA012) selected based on phenotypic characterization and stickiness (<15 cm) showed antibacterial activity against different pathogens with the highest activity found in TA004 (22.5 mm) and least in TA011 (16.6 mm). Furthermore, time-kill assay showed that the combined γPGA polymer was more effective and demonstrated bactericidal activity over individual γPGA which are bacteriostatic in nature. All γPGA polymer exhibited ACE properties except TA011. The highest IC50 was observed in TA006 (0.11 mg/ml) and least in TA004 (0.35 mg/ml). TA004 had the highest molecular weight (261 kDa) while TA011 had the least (194.97 kDa). In addition, all γPGA exhibited characteristic peaks at 3413-3268 cm−1 and 1722-1664 cm−1 that corresponded to amine N–H stretching intensities and C=O stretching in COOH. Bacillus isolates were identified as TA004 (B. subtilis-GenBank: MH782061), TA006 (B. amyloliquefaciens- GenBank: MH782075), TA011 (B. subtilis- GenBank: MH782088), TA012 (B. subtilis- GenBank: MH782083). OSL and LOSL have the potential for developing functional foods with a valuable effect on health.